Improving salt tolerance of lowland rice cultivar 'Rassi' through marker-aided backcross breeding in West Africa. (January 2016) - Bimpong, Isaac Kofi; Manneh, Baboucarr; Sock, Mamadou; Diaw, Faty; Amoah, Nana Kofi Abaka; Ismail, Abdelbagi M.; Gregorio, Glenn; Singh, Rakesh Kumar; Wopereis, Marco
Highlights: MAS was used to enhance salt tolerance of African cultivar 'Rassi'. 429 Saltol-ILs were identified as tolerant to salt stress at the vegetative stage. 16 Saltol-ILs had less yield loss (3–26%) after 4 seasons of field-testing. 8 Saltol-ILs showed high yield potential under stress and non-stress conditions. Abstract: Salt stress affects about 25% of the 4.4 million ha of irrigated and lowland systems for rice cultivation in West Africa (WA). A major quantitative trait locus (QTLs) on chromosome 1 (Saltol) that enhances tolerance to salt stress at the vegetative stage has enabled the use of marker-assisted selection (MAS) to develop salt-tolerant rice cultivar(s) in WA. We used 3 cycles of backcrossing with selection based on DNA markers and field-testing using 'FL478' as tolerant donor and the widely grown 'Rassi' as recurrent parent. In the BC3 F2 stage, salt-tolerant lines with over 80% Rassi alleles except in the region around Saltol segment were selected. 429 introgression lines (Saltol-ILs) were identified as tolerant at vegetative stage, of which 116 were field-tested for four seasons at the reproductive stage. Sixteen Saltol-ILs had less yield loss (3–26% relative to control trials), and 8 Saltol-ILs showed high yield potential under stress and non-stress conditions. The 16 Saltol-ILs had been included for further African-wide testing prior to release in 6 WA countries. MAS reduced the time for germplasm improvement from at least 7 to about 4 years. Our objective is to combine different genes/QTLs conferring tolerance to stresses under one genetic background using MAS.